Reflective functioning and emotion regulation in adolescents with a history of sexual offending: a comparative study with a non-offending control group - Mahdieh Pazhooyan; Fahimeh Fathali Lavasani; Zohreh Edalati Shateri; Komeil Zahedi Tajrishi (BMC, 2024)
Abstract Background Sexual offenses encompass a diverse array of behaviors across various contexts, affecting numerous individuals. Despite the prevalence of sexual offending among adolescents, there is still a limited understanding of this population. To contribute further to the literature in this field, the present study was conducted to compare a group of male adolescents convicted of sexual offenses with a control group in terms of reflective functioning (RF), emotion regulation (ER) strategies, and emotion dysregulation (ED). Methods 60 male adolescents aged 12 to 18 years (M = 16.90; SD = 0.97) who had been convicted of at least one serious sexual offense were recruited from male adolescents referred by juvenile courts to the Legal Medicine Organization in Mashhad, Iran, and compared with a control group of non-offending adolescents consisting of 60 male adolescents aged 12 to 18 years (M = 16.97; SD = 0.82) who were attending school. The groups were matched on age and education level. Results A comparison between these two groups revealed that adolescents with a history of sexual offending exhibited poorer RF capacity, greater use of suppression as an ER strategy, and higher scores in all ED domains (p's < 0.001) except non-acceptance of emotional responses compared with the control group. Conclusions Results suggest that RF, ER strategies, and ED need to be considered as important psychological factors in understanding and treating adolescents with a history of sexual offending.